LEARNING HISTORY OF WOMEN IN HISTORY EDUCATION FIS UNY - Nurpratiwi, Hany (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study is a qualitative research, to see and photograph the learning process Historyof Women in History Education Studies Program FIS UNY. Learning womenâs historyin History Education Prodi FIS UNY done through the assignment papers,presentations, class disscution , UTS and UAS. Lack of writing and historical researchthat deliberately describes the history of women should be of interest Womens Historycourse. So it is necessary to develop a model of learning through project-based learningto enhance the skills of writing the history of women on college campuses. Productsproduced later in the form of model of learning history through project based learningwhich includes cognitive, affective and psychomotor.Keyword: Womens History, Project Based Learning